Women’s College Decisions: How Much Does Marriage Matter? - Ge, Suqin (Journal of Labor Economics, 2011)
This article investigates the sequential college attendance decision of young women and quantifies the effect of marriage expectations on their decision to attend and graduate from college. A dynamic choice model of college attendance, labor supply, and marriage is formulated and structurally estimated using panel data from the NLSY79. The model is used to simulate the effects of no marriage benefits and finds that the predicted college enrollment rate will drop from 58.0% to 50.5%. Using the estimated model, the college attendance behavior for a younger cohort from the NLSY97 is predicted and used to validate the behavioral model.